Flower pattern formation of orchids: Case studies with respect to ABCDE model - Chakraborti, Mridul; Pal, Ram; Sailo, N; Kumar, Raj; Barman, D; Singh, D.R. (The Indian Journal of Genetics and Plant Breeding, 2016)
Orchids are known for their beautiful flowers with specialized organ identity and pattern formation. Genetic models for pattern formation of flowers are well established in actinomorphic flowers like Arabidopsis. However, the orchid flowers show zygomorphic symmetry and contain a highly differentiated labellum or lip. Besides, there is no marked difference in terms of structures of sepals and petals in many cases. The stamens and carpels are fused and form the column or gynostemium with anther cap containing pollinia at top. Few models like â€˜Orchid code theoryâ€™, â€˜Homeotic Orchid Tepal (HOT) modelâ€™, â€˜P-code modelâ€™ etc. have been proposed recently to explain genetic control of flower patterning in orchids. We have studied the suitability of those proposed models with some spontaneous bud variants as well as somaclonal variants showing alteration of floral organ patterns of all the flowers in the spike. The basic model of flower development with some alteration was found suitable in case of Cymbidium. Occurrence of structural male sterility due to mutation in B class homeotic gene in Cymbidium is also reported for the first time.The â€œP-codeâ€ model of perianth formation in orchids was found to be applicable for the recorded peloric mutants of Phalaenopsis. Few other variants of Eria tomentosa, Epidendrum sp. and Arundina graminifolia are also reported here. Whether all these changes are due to alteration of gene sequences or epigenetic mutations, needs to be verified in details.